Teachers and Their Participation Toward Distributed Leadership Practice in Secondary Schools, Yobe State Nigeria - Ibrahim, Saad; Ahmad, Asmah (Selangor Humaniora Review, 2019)
In many countries of the world education is considered as the backbone of development and schools can be seen as a place that shape societies and promote development. Leadership effects the success and failure of a school as an organisation. This makes school leadership more challenging. It has become more difficult for any single person to competently lead a school today. This has led to the recognition for collective school leadership model i.e. distributed leadership to improve school conditions in order to attain societal development. Distributed leadership supports shared responsibilities for effective leadership in schools. The purpose of this study was to find out leadership participation of teachers toward distributed leadership practices in the management of schools the from teachers’ perspective in Yobe State, Nigeria. Two hundred and twelve teachers completed a closed-ended questionnaire. The study employed descriptive statistical methods and used statistical package for Social Sciences (SPSS) version 20 for data analysis. Frequency, percentage and mean were used to find teachers’ level of participation in distributed leadership roles. The results indicated that teachers participate in distributed leadership practices at a moderate level. This revealed that teachers were given the opportunity to participate in leadership but not completely involved in school leadership roles. That is, they are not empowered to take ownership of their responsibilities. The findings have resulted in seeking for more improvement toward distributed leadership practice in schools.